Inefficiencies in water supply and perceptions of water use in peri-urban and rural water supply systems: case study in Cali and Restrepo, Colombia - Callejas Moncaleano, Diana Carolina; Pande, Saket; Haeffner, Melissa; Rodríguez Sánchez, Juan Pablo; Rietveld, Luuk (Frontiers in Water, 2024)
IntroductionWater scarcity is a significant global challenge that frequently manifests as inadequate water supply for domestic purposes. However, domestic water insecurity can occur even in regions where water is naturally abundant. Despite Colombia’s plentiful surface water resources, rural and peri-urban communities often experience limited access to water. Existing water supply systems are frequently susceptible to poor maintenance, particularly in remote areas where much of the infrastructure remains outdated. Consequently, water is often lost through leaks or unintentional non-domestic use. Although a regulatory framework for water usage exists, it does not consistently translate into effective implementation.MethodologyBased on an extensive survey of approximately 1000 households in four rural and four peri-urban communities in the Valle del Cauca Department, Colombia, we identified the factors underlying inefficient water supply and use. Perceived water use at the household level, based on self-reported time spent on various use types, such as bathing, and water supplied at the system level, was estimated.Results and discussionHousehold size, education level, age and occupation were found to be critical factors influencing end water use and water supply. This not only elucidates why water is supplied and used inefficiently in rural systems (e.g., due to non-domestic use), but also accounts for the variability of perceived water use within peri-urban systems. The water use perceived by households in the rural systems was statistically similar across the rural systems studied and was significantly lower than that in the peri-urban systems. Most rural systems exhibited very low ratios of perceived water use to water supplied, indicating that either water is lost in conveyance or that water is used for non-domestic purposes. Peri-urban users, who perceived to use more water than users in rural areas, were associated with younger and more educated households. Higher education levels were also associated with better financial capacity and technical ability to manage water systems; therefore, peri-urban systems were better managed.